Effect of Recognition, and Training and Development on Employee Performance - Budhathoki, Prem Bahadur; Shrestha, Shankar Kumar; Gurung, Anu; Maharjan, Matina (Nepalese Journal of Business and Management Studies, 2024)
This study examines the impact of recognition, training and development on employee performance. The study used a descriptive and casual research approach to investigate the hypotheses developed for the study and to represent the general knowledge of respondents. Additionally, cross sectional primary source of data was gathered from the main sources. The structured questionnaires were disseminated to target respondents of employees working in Cooperative sector in Nayabazar, Kathamndu and utilized 102 data for the analysis. For the investigation, a non-probability convenience sampling method was used. Furthermore, the data was analyzed using inferential methods and descriptive statistics. The finding of the study revealed that employee performance is positively and significantly impacted by recognition. Likewise, training and development have a favorable and substantial impact on employee performance. These findings exhibit that employee performance improves as training, development, and recognition increase. Subsequently, the results of this research may serve as a standard for management of human capital in firms that adopt ways to improve employee performance. Policymakers and other stakeholders can adopt these insights to enhance worker performance. These results can contribute to the existing theories.